PEMANFAATAN LIMBAH KULIT KENTANG (Solanum tuberosum L.) UNTUK PEMBUATAN BIOETANOL DENGAN METODE HIDROLISA ASAM (HCL) - Betti Rosita (JURNAL KESEHATAN PERINTIS, 2017)
Waste from processing food ingredients, such as potato skin. Potato skin is one example of raw material for making biethanol because potato skin contains a lot of starch, cellulose, hemicellulose, lignin and sugar. Bioethanol is a liquid from the fermentation process of sugar from a source of carbohydrates (starch) using the help of microorganisms, bioethanol can be used as a substitute for fuel oil (BBM) depending on the level of purity. One example of raw material for making biethanol is waste or waste left over from processing food ingredients, such as potato skin. Potato skin can be made bioethanol because it contains a lot of starch, cellulose, hemicellulose, lignin and sugar. In this study the aim was to find out how much bioethanol levels produced from potato skin waste treatment using the hydolisa acid method using HCl to hydrolyze potato skin into glucose and the fermentation method using Saccharomyces cerevisiae because it has very high conversion to ethanol. The parameters tested were the determination of optimum fermentation time on the percentage of ethanol (2,4,6,8 and 10 days), determining the percentage of ethanol to variations in the concentration of acid (HCl) (0.2, 0.4, 0.6, 0.8 and 1 M) and determining glucose levels . From the research, the optimum fermentation time on the 8th day resulted in a percentage of ethanol 4.1% and the optimum percentage of ethanol at 0.6 M acid concentration (HCl) produced a percentage of 4.1% ethanol with a glucose level of 8.65%.